Rare desmoplastic trichilemmoma associated with sebaceous nevus - Márcio Martins Lobo Jardim; Bruno de Castro e Souza; Renata Cavanellas Fraga; Rafael Cavanellas Fraga (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Nevus sebaceous of Jadassohn is a congenital hamartoma that usually affects the scalp and face. Several benign or malignant neoplasias may develop in the lesion and the most common are trichoblastoma, syringocystadenoma papilliferum, and basal cell carcinoma. Trichilemmoma is a benign solid tumor originating from external sheath cells of pilosebaceous follicles. When it is characterized by a central zone of desmoplasia, it is called desmoplastic trichilemmoma. We report a case of a 58-year-old patient who developed a tumor in a sebaceous nevus. We performed a total excision of the lesion. Histopathological diagnosis was compatible with desmoplastic trichilemmoma. Our literature review reveals that the occurrence of trichilemmoma desmoplastic is unusual. Moreover, it can mimic an invasive carcinoma on histological and clinical examinations. This fact confirms the importance of reporting the occurrence of this rare cancer in a nevus sebaceous of Jadassohn.